Sufficiency in social practices: An underestimated potential for the transformation to a circular economy - Suski, Pauline; Palzkill, Alexandra; Speck, Melanie (Frontiers in Sustainability, 2023)
To date, the circular economy has fallen short of its promise to reduce our resource demand and transform our production and consumption system. One key problem is the lack of understanding that highly promising strategies such as refuse, rethink, and reduce can be properly addressed using research on sufficiency. This article argues that a shift in focus is required in research and policy development from consumers who buy and handle circularly designed products to consumption patterns that follow the logic of sufficiency and explain how sufficiency-oriented concepts can be incorporated into existing social practices. The authors show that sufficiency is not necessarily as radical and unattractive as is often claimed, making it a suitable yet underrated strategy for sustainability and the transition to an effective circular economy. The case of urban gardening shows that small interventions can have far-reaching effects and transform consumption patterns as the logic of availability is contested by newly developed concepts of “enoughness” and opposition to “über-availability.” The authors propose utilizing comprehensive state-of-the-art theories of consumption and human action when developing strategies and policies to make the circular economy sustainable while being more critical of utilitarian approaches. Using social practice theories that have proven to be beneficial allows human actions to be comprehensively analyzed by recognizing their embeddedness in social and material frameworks; addressing the meaning, competences, and materials of routinized human behavior; and examining indirect effects.